Erxian Decoction Attenuates TNF-α Induced Osteoblast Apoptosis by Modulating the Akt/Nrf2/HO-1 Signaling Pathway - Wang, Nani; Xin, Hailiang; Xu, Pingcui; Yu, Zhongming; Shou, Dan (Frontiers in Pharmacology, 2019)
Erxian decoction (EXD), a traditional Chinese medicine formula, has been used for treatment of osteoporosis for many years. The purpose of this study was to investigate the pharmacological effect of EXD in preventing osteoblast apoptosis and the underlying mechanism of prevention. Putative targets of EXD were predicted by network pharmacology, and functional and pathway enrichment analyses were also performed. Evaluations of bone mineral density, serum estradiol level, trabecular area fraction, serum calcium levels and tumor necrosis factor (TNF)-α levels in ovariectomized rats, as well as cell proliferation assays, apoptosis assays, and western blotting in MC3T3-E1 osteoblasts were performed for further experimental validation. Ninety-three active ingredients in the EXD formula and 259 potential targets were identified. Functional and pathway enrichment analyses indicated that EXD significantly influenced the PI3K-Akt signaling pathway. In-vivo experiments indicated that EXD treatment attenuated bone loss and decreased TNF-α levels in rats with osteoporosis. In-vitro experiments showed that EXD treatment increased cell viability markedly, decreased levels of caspase-3 and the rate of apoptosis. It also promoted phosphorylation of Akt, nuclear translocation of transcription factor NF-erythroid 2-related factor (Nrf2) and hemeoxygenase-1 (HO-1) expression in TNF-α-induced MC3T3-E1 cells. Our results suggest that EXD exerted profound anti-osteoporosis effects, at least partially by reducing production of TNF-α and attenuating osteoblast apoptosis via Akt/Nrf2/HO-1 signaling pathway.